Theoretical background and implementation of the finite element method for multi-dimensional Fokker–Planck equation analysis. (November 2017) - Král, Radomil; Náprstek, Jiří
Highlights: Overall computational strategy for stochastic analysis of nonlinear multi-DOF dynamic systems. Description of multi-dimensional Finite Element mesh generator adapted for Fokker-Planck equation solution. Numerical or closed-form spatial integration of simplex element in n-dimensional space. Probability space integration method for visualization of 2-D conditional probability. Abstract: Fokker–Planck equation is one of the most important tools for investigation of dynamic systems under random excitation. Finite Element Method represents very effective solution possibility particularly when transition processes are investigated or more detailed solution is needed. However, a number of specific problems must be overcome. They follow predominantly from the large multi-dimensionality of the Fokker–Planck equation, shape of the definition domain and usual requirements on the nature of the solution which are out of a conventional practice of the Finite Element employment. Unlike earlier studies it is coming to light that multi-dimensional simplex elements are the most suitable to be deployed. Moreover, new original algorithms for the multi-dimensional mesh generating were developed as well as original procedure of the governing differential and algebraic systems assembling and subsequent analysis. Finally, an illustrative example is presented together with aspects typical for the problem with large multi-dimensionality.